Impact of Motivations in Choosing English Education Department and Academic Achievement - Nuraeningsih Nuraeningsih; Suprihadi Suprihadi (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Not all graduates of English Education Department, Teacher Training and Education Faculty, Universitas Muria Kudus work as teachers or in the field of education. The objectives of this research are: 1) to explore the motivation of the students in choosing English Education Department Universitas Muria Kudus, 2) to test the significance of the difference between the academic achievements of integrative-motivated students and those of instrumental-motivated students. The design of this research is qualitative-quantitative with motivation as the independent variable and academic achievement as the dependent variable. Questionnaire was used to collect the data from 81 students as the subjects of the research. Descriptive statistical analysis was used to achieve the first objective and t-test was used to achieve the second objective. The results of the research show that: 1) the dominant motivation of the students in choosing English Education Department Universitas Muria Kudus is integrative; 2) there is a significant difference of academic achievement of the instrumental-motivated students and that of integrative-motivated students, that is, the academic achievement of the students who have integrative motivation is better than that of the students who have instrumental motivation.